Inferring Beliefs and Desires From Emotional Reactions to Anticipated and Observed Events - Wu, Yang (Child Dev, 2017)
Researchers have long been interested in the relation between emotion understanding and theory of mind. This study investigates a cue to mental states that has rarely been investigated: the dynamics of valenced emotional expressions. When the valence of a character's facial expression was stable between an expected and observed outcome, children (N = 122; M = 5.0 years) recovered the character's desires but did not consistently recover her beliefs. When the valence changed, older but not younger children recovered both the characters’ beliefs and desires. In contrast, adults jointly recovered agents’ beliefs and desires in all conditions. These results suggest that the ability to infer mental states from the dynamics of emotional expressions develops gradually through early and middle childhood.